PEMBUATAN BIODIESEL DARI MINYAK JARAK PAGAR (Jatropha Curcas) DENGAN KATALIS ASAM POLISTIRENA SULFONAT (PSS) 4% DAN 8 % PADA SUHU 1200C SELAMA 6 JAM - Mardiansyah, Dedi (Edu Research, 2012)
transesterification process. The castor oil was previously tested for titration and produced 77,78 % free fatty acid. The process was done in a autoclave by mixing the materials of castor oil to methanol in 1:12 mole. The reaction use 4 % and 8 % of PSScatalyst in 1200C for 6 hours. The solution was neutralized by ammoniac and estracted by n-hexane. The transesterification resulted in 2 layers: upper layer containing methyl ester (FAME) and the lower layer containing residual glycerol and methanol and than separated.